DNA aptamer assemblies as fibroblast growth factor mimics and their application in stem cell culture. Issue 18 (12th February 2019) - Ueki, Ryosuke; Atsuta, Saki; Ueki, Ayaka; Hoshiyama, Junya; Li, Jingyue; Hayashi, Yohei; Sando, Shinsuke
Abstract : A 76-mer single-stranded DNA acts as functional mimic of basic fibroblast growth factor (bFGF), one of the essential factors for stem cell culture. Abstract : Replacing expensive and thermally unstable growth factors with synthetic alternatives has been an important issue in stem cell-based regenerative medicines. Here we developed DNA aptamer-assemblies that act as functional mimics of basic fibroblast growth factor (bFGF), one of the essential factors for stem cell culture. The most potent aptamer assembly named TD0, composed solely of 76-mer single-stranded DNA, could support the self-renewal and pluripotency of induced pluripotent stem cells (iPSCs). This work presents the first application of DNA aptamer in the maintenance of iPSCs.